319 Phase II trial of immunotherapy in primary glioblastoma: antigens from self-renewing autologous tumor cells presented by autologous dendritic cell vaccine. (9th November 2020) - Bota, Daniela; Piccioni, David; Duma, Christopher; LaRocca, Renato; Kesari, Santosh; Carrillo, Jose; O'Donnell, Robert; Aiken, Robert; Hsu, Frank; Kong, Xiao-Tang; Taylor, Thomas; Nistor, Gabriel; et al.
Abstract : Background: Primary glioblastoma (GBM) is associated with poor survival. Adjunctive vaccines may improve survival by inducing or enhancing anti-GBM immune responses. Methods: A multi-institutional phase II clinical trial was conducted with a primary objective of 75% survival 15 months after intent-to-treat enrollment. Key eligibility criteria were: (1) primary GBM diagnosis, (2) age < 70 years at time of tumor resection, (3) successful GBM cell culture, (4) successful monocyte collection by leukapheresis, (5) Karnofsky Performance Status (KPS) > 70 after surgical recovery. Dendritic cells (DC) were differentiated from autologous monocytes, then incubated with autologous tumor antigens (ATA) from the GBM cell line-lysate to produce each patient-specific DC-ATA vaccine. Doses were suspended in 500 mcg granulocyte-macrophage colony-stimulating factor (GM-CSF) at the time of subcutaneous injections at weeks 1, 2, 3, 8, 12, 16, 20 and 24. Patients were enrolled just prior to starting standard concurrent temozolomide (TMZ) and radiation therapy (RT) for the intent-to-treat after recovery from RT/TMZ. Results: Tumors were collected August 2018-January 2020. Cell line success rate was 71/73 (97%); monocyte collection success rate was 63/65 (97%), but 10 patients required a second leukapheresis. Patients were enrolled for in-to-treat October 2018-February 2020. The 60 patients included 42 men and 18 women with median age of 59 years (range of 27–70). Racial make-up was 43 White, 10 Hispanic, 2 Black, 1 Asian and 3 Other. KPS was 100 in 4, 90 in 25, 80 in 17 and 70 in 14 (mean 83.2). MGMT methylation was present in 13, absent in 31, and unknown in 16; IDH mutation was present in 7, absent in 50, and unknown in 3. 57 patients had received 380 doses with 9 still under treatment at time of abstract submission. 32 had completed all 8 doses; 16 had received fewer than 8 doses when they discontinued treatment. No patient discontinued treatment because of toxicity, but 28 have been hospitalized for 53 treatment-emergent central nervous system-related serious adverse events including seizures (15 episodes), falls and/or increased focal weakness (13 episodes), or severe headaches or visual changes (3 episodes). Conclusions: This patient-specific DC-ATA approach is feasible and may be increasing intratumor inflammation that is associated with on-target efficacy and/or toxicity. An interim survival analysis will be conducted in October 2020, 15 months after the median patient was enrolled; results will be available November 2020 as will immunologic data for 55 patients who received at least two injections. Trial Registration: Clinicaltrials. gov NCT03400917 . Ethics Approval: The study was approved by UCI IRB, approval number 2018-4148.